IMPLEMENTASI ALGORITMA ALPHA SKIP SEARCH PADA PERANCANGAN APLIKASI KITAB AL-HIKAM BERBASIS ANDROID - Syahman Nasution (Fakultas Teknologi Lingkungan dan Mineral - Universitas Teknologi Sumbawa, 2021)
The kitab comes from Arabic which means writing, the meaning of the term book is the writing of revelation on sheets that are collected into one book form. Kitab Al-Hikam is the work of Sheikh Ibn-Atha'illah, the third murshid of Tariqah Syadziliyah. Kitab Al-Hikam is intended for travelers (salik), which contains further guidance for every traveler to take a spiritual journey. Kitab Al-Hikam discusses monotheism and morals that lead to Islamic Sufism. Kitab Al-Hikam contains a variety of strict mystic terminology, which refers to various terms in the Qur'an and has a very large number. The problem that often occurs in this research is the difficulty in finding the results of the search for the contents of the Kitab Al-Hikam which refers to various terms in the Qur'an and has a very large number for Muslims. Thus making it difficult for many Muslims to find search results for certain sections of the book in a fast and precise time to understand. Alpha Skip Search algorithm is one of the string-matching algorithms which is the development of the skip search algorithm. The Android-based Al-Hikam application by applying the alpha skip search algorithm is considered very effective to make it easier to learn and understand the contents of the Al-Hikam book because it can be operated anywhere and anytime online or offline. Overcoming these problems, the author designed an android-based Kitab Al-Hikam application using the eclipse juno editor and SQLite database. To minimize the time needed to search for the contents of the designed Al-Hikam book, the author applies the Alpha Skip Search algorithm to make it easier for Muslims to search for the contents of the Al-Hikam book to be studied and understood.